CARTESIAN SUBJECTS LOST IN THE ALPS REFLECTIONS ON RUBEN ÖSTLUND’S FORCE MAJEURE - Johansson, Sven Anders (The Nordic Journal of Aesthetics, 2018)
The article analyses the constitution of subjectivity in Ruben Östlund’s film Force Majeure (2014). At the centre of attention stands the male protagonist who is uncapable of reconciling his inner nature with the external expectations. If the film may be un- derstood as a critique of existing middle-class conventions, it also reproduces a highly conventional ideal of the self-identical subject. The article argues that this confusion or irony is an expression of a Cartesian subject – still prevalent in the film – in crisis. A neglected aspect of Descartes’ theory is that the autonomy of the subjects presupposes the existence of God. The problem for Östlund’s char- acters is that there is no God. Still, they act as if he, or as if any au- thority might, legitimize their subjectivity. Thus, the whole existence becomes a series of performances. The idea of an inner nature cor- responds with the notion of an outer nature. The latter is certainly very present in Force Majeure, but at the same time this nature is constantly problematized. On an allegorical level, the film may thus be read as a comment on the Anthropocene, a state where we no longer know neither what “nature”, nor “culture” is.